The memory of the Spanish Civil War in Basque nationalism (1937-1960) - Martínez Rueda, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In the Basque Country, during the post-war period, an unequal combat between two opposing memories of the Civil Spanish War began: the official Franquista memory and the clandestinenationalist memory. This article studies the elaboration and transmission process of this clandestine memory formulated by the Basque nationalist community between 1937 and 1960. We analyzed which were the elements of the nationalist account and identified the main agents that made its spread possible. For this, we studied a wide range of documental sources: speeches of the political authorities in exile, writings of the Basque clergy, testimonials from veterans, nationalist press, literary works and historiographic works. The article concludes that by 1960, the battle between the official Franquista memory and the nationalist clandestine memory was resolved in favor of the latter. The patriotic and epic narrative of the warlike past elaborated by the nationalist community was assumed by the new nationalist generations socialized in the post-war era. This situation contrasts with what happened around Spain, where the defeated did not manage to spread an alternative unitary memory to the narration of the crusade and the new generations tended to repudiate the memory of the Civil War, monopolized by the Franquista regime. This particular memory of the war whichwas rooted in the political culture of Basque nationalism was one of the factors that explained the singular historical evolution of the Basque Country during the late Franquismo and the transition to democracy.